A study on the influence of human resource factors and Human Resouces Management (HRM) practices on employees’ intention to stay: A case study In Koperasi Permodalan Felda Malaysia Berhad / Nik Nur Masitah Mohamed Nor - Mohamed Nor, Nik Nur Masitah (Bachelor of Science (Hons) Statistics, 2015)
The purpose of this study is to examine the relationships between human resource factors and Human Resources Management (HRM) practices toward employees’ intention to stay. Three dimensions of human resource factors (Remuneration and Recognition, Training and Career Development, and Challenging Employment Assignment and Opportunities) and Human Resource Management (HRM) practices were assessed as the predictors in this study. A total of 203 questionnaires were distributed to employees in Koperasi Permodalan FELDA Malaysia Berhad, Kuala Lumpur and the questionnaires returned were used for the data analysis. The findings reported a positive and significant correlation of all independent variables and intention to stay. The coefficient determination of multiple regression model indicated that 84.9 percent of variance that explained the employees’ intention to stay was accounted for by Training and Career Development, and Challenging Employment Assignment and Opportunities. This study found that Training and Career Development, and Challenging Employment Assignment and Opportunities are significantly associated to employees’ intention to stay Discussions elaborated on the importance each Training and Career Development, and Challenging Employment Assignment and Opportunities in promoting intention to stay among the employees